Athenry Dominican Priory, south nave wall, niche, arch and hood - O'Donovan, Danielle (My University, 2008)
Arch and hood moulding of westernmost niche of south nave wall. Arch moulding from inner surface comprises: chamfer, flat surface, hollow, roll-and-fillet, roll, hollow, chamfer, flat surface of wall. The hood, from outside face to inner comprises: roll-and-fillet, hollow, chamfer. The style of this moulding can best be described as debased Early English. The roll-and-fillet is particularly deformed.
Niche
Keywords: Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Architecture, Dominican; Late Medieval; roll-and-fillet moldings; moldings, hollow; fillets (moldings)